Avian Trichomoniasis Prevalence in Domesticated Pigeons in Thi-Qar Province, Iraq - Jaafar, Ahmed (University of Thi-Qar Journal of agricultural research, 2023)
Abstract | Avian trichomoniasis is a disease that is spread globally in wild and domesticated birds, especially pigeons, caused by the parasite Trichomonas gallinae and known as canker. The complications of this illness include lesions in the upper gastrointestinal tract. The present study's goal would be to study the prevalence of T. gallinae in domesticated pigeons in Thi-Qar province, Iraq, utilizing the internal transcribed spacer1-5.8s rRNA-internal transcribed spacer2 gene. A total of 405 pigeons including 160 of Alzajil pigeons, 160 of red pigeons and 85 of Arafali pigeons were collected from local markets for the period from September 2022 to May 2023, the infection rates were 38.13, 37.50, and 42.35 respectively. The study noted a non-significant difference at p. value < 0.05 in distribution of T. gallinae according to bird's species. The study found that infection rate is higher in squabs than adults in all pigeons of the three groups. There was no effect of sex on the prevalence rates. As for the months in which the samples were collected the study found there is significant difference at p. value < 0.05 of parasite distribution according to collection months, the highest infection rate was recorded in November 68.89 while the lowest isolated parasite was in April 17.78. Key words | Thi-Qar province, avian trichomoniasis, pigeons, light microscope.